2008
DOI: 10.1590/s1516-18462008000300012
|View full text |Cite
|
Sign up to set email alerts
|

Processamento auditivo, resolução temporal e teste de detecção de gap: revisão da literatura

Abstract: TEMA: processamento auditivo temporal e resolução temporal. OBJETIVO: realizar revisão teórica sobre processamento auditivo e resolução temporal, bem como sobre os diferentes parâmetros de marcadores utilizados em testes de detecção de gap e como eles podem interferir na determinação dos limiares. CONCLUSÃO: o processamento auditivo e a resolução temporal são fundamentais para o desenvolvimento da linguagem. Em virtude dos diferentes parâmetros que podem ser utilizados no teste em questão, os limiares de detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 27 publications
2
35
1
25
Order By: Relevance
“…The data revealed that subjects presented a very similar performance for both types stimuli used in the RGDT test: the click and the pure tone. When comparing the RGDT test results obtained for the pure tone and click stimuli in this study to those in the reviewed literature, it was observed that the mean final temporal acuity threshold and the clicks in this study highly resemble those described by many other authors (5,(10)(11)(12)(13)(14) when a normal hearing population was studied. The mean final temporal acuity thresholds obtained at other studies in the literature with a population of similar age range to the one in the present study is between 4.77 ms and 12.2 ms (11,(13)(14)(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The data revealed that subjects presented a very similar performance for both types stimuli used in the RGDT test: the click and the pure tone. When comparing the RGDT test results obtained for the pure tone and click stimuli in this study to those in the reviewed literature, it was observed that the mean final temporal acuity threshold and the clicks in this study highly resemble those described by many other authors (5,(10)(11)(12)(13)(14) when a normal hearing population was studied. The mean final temporal acuity thresholds obtained at other studies in the literature with a population of similar age range to the one in the present study is between 4.77 ms and 12.2 ms (11,(13)(14)(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 74%
“…Temporal processing, or the temporal aspects of hearing, may be defined as the perception of sounds and their modification in a determined time interval (4,5) . The categories of temporal processing are: the abilities of temporal ordering or sequencing, temporal resolution or discrimination, temporal integration and temporal masking (4,6) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vanessa Aparecida Arseno (1) Cristiane Aparecida de Carvalho (1) Mônica Pires de Castro (1) Sinésio Grace Duarte (1) Ana Cláudia Mirândola Barbosa Reis (2) Antônio Carlos Marangoni (1) Lucinda Maria de Fátima Rodrigues Coelho (1) …”
Section: Estudo Comparativo Dos Resultados De Testes De Resolução Temunclassified